A nationwide study on the prevalence of functional gastrointestinal disorders in school-children - Miguel Saps; Jairo Enrique Moreno-Gomez; Carmen Rossy Ramírez-Hernández; John M. Rosen; Carlos A. Velasco-Benitez (Permanyer, 2017)
Introduction: Functional gastrointestinal disorders (FGIDs) are highly prevalent worldwide and are thought to result from the interplay of multiple factors that can vary from region to region. Nationwide studies can help understand the regional epidemiology and the pathogenesis of FGIDs. The objectives of this study were to determine the prevalence of FGIDs in school-children of Colombia and assess associated factors. Methods: A cross-sectional study was carried out at twelve private and public schools in ten cities distributed through the four main geographic regions of Colombia. School-children completed a validated questionnaire to assess functional gastrointestinal disorders according to Rome III criteria. Demographic information and past medical and family history was obtained from the parents. Results: A total of 4394/5062 (86.8%) children participated in the study, with ages ranging from 8-18 years (mean = 11.9, SD = 2.3). The percentage of children with al least on FGID was 23.7%. Disorders of defecation were the most common category FGID (11.7%) followed by abdominal pain related-functional gastrointestinal disorders (10.4%). Children have increased odds of FGIDs if they have separated parents (OR 1.22, P=0.007), attend private school (OR 1.54, P<0.001), or have nausea (OR 3.16, P<0.001). Conclusions: This large epidemiological study of pediatric FGIDs is the first to evaluate a broad cross-section of children throughout a nation in the Americas. High prevalence of FGIDs and identified associations with their likelihood are relevant when providing medical care and when planning public health efforts.